2014
DOI: 10.2147/ijn.s59779
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial cell adhesion molecule aptamer functionalized PLGA-lecithin-curcumin-PEG nanoparticles for targeted drug delivery to human colorectal adenocarcinoma cells

Abstract: To improve the efficacy of drug delivery, active targeted nanotechnology-based drug delivery systems are gaining considerable attention as they have the potential to reduce side effects, minimize toxicity, and improve efficacy of anticancer treatment. In this work CUR-NPs (curcumin-loaded lipid-polymer-lecithin hybrid nanoparticles) were synthesized and functionalized with ribonucleic acid (RNA) Aptamers (Apts) against epithelial cell adhesion molecule (EpCAM) for targeted delivery to colorectal adenocarcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 39 publications
(47 reference statements)
0
21
0
Order By: Relevance
“…The superior antitumor effect of Co-FA-NPs could be attributed to the targeting, the enhanced nanoparticles stability during the blood circulation, the sufficient and coinstantaneous delivery of two drugs to the tumor site, the efficient cellular uptake in the tumor, and the synergistic effect of CDDP and PTX on tumor inhibition. [ 40 ]…”
Section: Resultsmentioning
confidence: 99%
“…The superior antitumor effect of Co-FA-NPs could be attributed to the targeting, the enhanced nanoparticles stability during the blood circulation, the sufficient and coinstantaneous delivery of two drugs to the tumor site, the efficient cellular uptake in the tumor, and the synergistic effect of CDDP and PTX on tumor inhibition. [ 40 ]…”
Section: Resultsmentioning
confidence: 99%
“…Instead of developing new drugs, these studies explored a potential effective strategy that utilises a CSC-targeting moiety to deliver existing chemotherapeutic agents to eradicate both non-CSCs and CSCs. Most recently, RNA aptamers for targeting CSC markers (EpCAM and CD133) have been isolated 49 , 60 , 219 . Upon binding to cancer cells expressing these CSC markers, these CSC-targeting aptamers efficiently internalised via receptor-mediated endocytosis, an important mechanism capable of bypassing ATP-binding cassette transporters (ABC transporters) that are responsible for multiple drug resistance in CSC 60 , 100 .…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In addition, the surface of PLGA nanoparticles can be modified with targeting moieties such as antibodies, proteins, and small molecules. [11] The present study found that the A10 aptamer-modified PLGA nanoparticles target to prostate cancer cells and are more effective at silencing the expression of the AR gene and decreasing cell viability than other treatments. We also found that the particle size, zeta potential and loading efficiency of TFO were not obviously changed, which is of great value for future clinical use.…”
Section: Discussionmentioning
confidence: 52%